Criticism of Digital Native Students in Responding to Local Digital Democracy: Kritikalitas Mahasiswa Digital Native dalam Menyikapi Demokrasi Digital Lokal - Badariah, Putri Pujiati Nuri; Saleh, Syarbaini (Indonesian Journal of Innovation Studies, 2025)
General background: In the digital era, the rapid development of technology and internet access has transformed how individuals engage with information and democratic processes. Specific background: Among digital natives, especially university students, digital platforms are a primary medium for political engagement. Knowledge gap: Previous research has generally overlooked the specific relationship between digital literacy competence and democratic literacy in the context of local elections and political participation among Generation Z. Aims: This study investigates the role of digital literacy in shaping democratic literacy among students of the Tadris IPS Program at UIN Sumatera Utara, particularly in relation to the 2024 gubernatorial election. Results: Findings indicate that students demonstrate fundamental digital literacy skills, moderate democratic awareness, and varied perceptions of Bobby Nasution’s election victory, influenced by digital media exposure. Novelty: This research provides a qualitative exploration of how digital natives interpret political events through digital literacy lenses, emphasizing the local context and students’ experiential insights. Implications: The study underscores the need for integrated digital-democratic literacy curricula in higher education to foster critical, informed, and participatory citizens in democratic societies.Highlight : The study highlights how digital literacy skills influence students’ ability to filter and critically assess political information. Students’ perception of political events, such as Bobby Nasution’s election, is shaped by exposure to social media. Integration of digital and democracy education is essential to foster critical thinking and civic engagement in digital natives. Keywords : Digital Literacy, Democracy Literacy, Student Participation, Media Influence, Political Perception